A morte em São Borja: relatórios e registros de óbitos numa região de fronteira (1889-1930) - Nunes, Janilton Fernandes (2020)
This thesis addresses the ways of living and dying in São Borja in the Old Republic, defending that these were marked by the situation of border between countries, by the currency river and its uniqueness, but mainly due to the forms of political-administrative management managers of the municipality, after the creation of the local Organic Law. Considering the notary records that certify deaths in the city, the study analyzes the political, budgetary, fiscal, etc. deliberations that make it possible deepen the understanding of daily life in the city. Together, these sources were essential. to understand the ways of daily living and how dying was configured in a unique way in the locality of São Borja, in the period of the so-called Old Republic (1889-1930). For the organization and development of the research, it was generated, with the data from these main primary sources, a set of dynamic information, under form of an information bank based on an electronic spreadsheet, capable of articulating with other sources. In this sense, the existing works that involved the location and period, as well as research in other locations with similar methods. To do so, it opens ¿ through a catalogue, created by research - the possibility of knowing the details of death records, making feasible to analyze their meanings, such as what the death records reveal and the inconsistency of information in the daily records of the municipal administration events in the community by other ways of obtaining information. THE research started from a primary source, in this case, the death records of the local registry, to counterpoint and evaluate their information about daily life involving death, bringing such data and information to give more support to the study, succeeding the search of clarification in the face of criticism and the comparison of similar acts and facts in the locality or in other communities. As theoretical-methodological contributions, we resorted to discussions of civil records, elements of serial and quantitative history, and studies demographics, as well as discussions on the history of health and analyzes of borders and preexisting approaches to São Borja. The investigation highlighted the situation and the difficulties of time lived in the delimited space of individuals on the São Borja border through legal records, authors and historians linked to the study of the region of the southern border of Brazil, confirming the hypothesis of the link between the deaths and the public investment made in the municipality.